Experimental and smoothed particle hydrodynamics analysis of interfacial bonding between aluminum powder particles and aluminum substrate by cold spray technique - Manap A.; Okabe T.; Ogawa K.; Mahalingam S.; Abdullah H. (Springer London, 2023)
Adhesives; Aluminum; Aluminum coatings; Aluminum powder metallurgy; Bonding; Deposition; High resolution transmission electron microscopy; Ion beams; Models; Morphology; Numerical methods; Scanning electron microscopy; Velocity; Velocity control; Cold spray; Cold spray techniques; Impact behavior; Interface morphologies; Interfacial bonding; Particle deformation; Smoothed particle hydrodynamics; Smoothed particle hydrodynamics methods; Hydrodynamics